The changes in financial support for agrienvironmental programme in Poland - Karol Kociszewski (Economic and Environmental Studies (E&ES), 2016)
The membership in the European Union (EU) created favourable conditions for the implementation of the agri-environmental programme (AEP) in Poland. The AEP is the most important rural development measure in the UE (in terms of financial support). The goal of the paper is to assess the effectiveness related to the absorption of the funds for the AEP in Poland. That effectiveness was analysed in the context of the scope and the way in which Polish authorities took advantage of opportunities from the EU financial support which was available to be spent on that measure. The Author used descriptive and comparative analysis to show differences in absorption of financial sources in Poland and in the entire EU for three time periods chosen due to the stages of multiannual financial perspectives for the Common Agricultural Policy: 2004-2006, 2007-2013, 2014-2020. The effectiveness of absorption of the AEP is relatively low - especially in comparison to the groups of the EU member states divided due to the date of accession (after or before 2004). The share of expenditures on the AEP in Polish Rural Development Programme (in all discussed time periods) is one of the lowest in the EU. The effectiveness is also low when we take into account the relation of executed expenditures on the AEP to the allocations which were potentially available for it. It especially refers to the first period of the EU membership. In the second period the effectiveness was improved, but it was worsened again in years 2014-2020 as a result of decisions made by Polish authorities. The biggest possible part of funds for rural development was reallocated for direct payments and consequently the possibilities of further development in implementation of the AEP were strongly reduced.
Keywords: O13; Q15; Q18; Q57; 330; sustainable agriculture and rural development; Sustainable Agriculture; rural development; rural development measures; agri-environmental programme